Buddhist dynamics in premodern and early modern Southeast Asia - Lammerts, D. Christian (ISEAS, 2015)
The study of historical Buddhism in premodern and early modern Southeast Asia stands at an exciting and transformative juncture. Interdisciplinary scholarship is marked by a commitment to the careful examination of local and vernacular expressions of Buddhist culture as well as to reconsiderations of long-standing questions concerning the diffusion of and relationships among varied texts, forms of representation, and religious identities, ideas, and practices. The twelve essays in this collection, written by leading scholars in Buddhist Studies and Southeast Asian history, epigraphy, and archaeology, comprise the latest research in the field to deal with the dynamics of mainland and (pen)insular Buddhism between the sixth and nineteenth centuries C.E. Drawing on new manuscript sources, inscriptions, and archaeological data, they investigate the intellectual, ritual, institutional, sociopolitical, aesthetic, and literary diversity of local Buddhisms, and explore their connected histories and contributions to the production of intraregional and transregional Buddhist geographies.